Verbal-Visual Indicators of Genre Identification in a Mediotext (Using Monologised Audiovisual Interviews as an Example) - Szkudlarek-Śmiechowicz, Ewa (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2023)
The aim of this article is to typify the verbal and visual means that determine whether a media expression, seemingly monologic in form, fits the interview genre. The research material consists of monologued audiovisual interviews of a confessional nature from the series “Room Number Seven” published on YouTube. Given the repetitive and cyclical nature of vlogs, the monologued interview in an audiovisual platform like YouTube evolves into a sub-genre with a relatively stable set of features. These characteristics no longer define individual messages but rather shape the content in a serial format. Internet user comments on selected episodes from the series “Room Seven” clearly demonstrate that, for viewers, monologued confidences are an unconventional demonstration of the interview genre pattern.